Hayek and the evolution of capitalism - Beck, Naomi, 1975- (Chicago ; London : The University of Chicago Press, 2018)
Few economists can claim the influence - or fame - of F.A. Hayek. Winner of the Nobel Prize, Hayek was one of the most consequential thinkers of the twentieth century, his views on the free market echoed by such major figures as Ronald Reagan and Margaret Thatcher. Yet even among those who studied his work in depth, few have looked closely at his use of ideas from evolutionary science to advance his vision of markets and society. With this book Naomi Beck offers the first full-length engagement with Hayek's thought from this perspective. Hayek argued that the capitalism we see in advanced civilizations is an unintended consequence of group selection--groups that adopted free market behavior expanded more successfully than others. But this attempt at a scientific grounding for Hayek's principles, Beck shows, fails to hold water, plagued by incoherencies, misinterpretations of the underlying science, and lack of evidence. As crises around the globe lead to reconsiderations of the place of capitalism, Beck's excavation of this little-known strand of Hayek's thought - and its failure - is timely and instructive.
Introduction: F.A. Hayek the avant-garde conservative -- The road to evolution -- From complexity to order -- Believe and prosper -- Economic progress and its discontents -- Conclusion: the battles of yesterday.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Hayek, Friedrich A. von -- 1899-1992.; Hayek, Friedrich A. von -- 1899-1992; Free enterprise; Capitalism; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Capitalism; Free enterprise